Inhibition of Tyrosinase Activity on Dopamine Hydrochloride by Kojic Acid - Sariri, R.; Moghimi, R.; Ranjbar, R.B. (Asian Journal of Chemistry, 2010)
The inhibition effect of kojic acid on tyrosinase activity was tudied and the rate of enzymatic reaction in presence and absence of the inhibitor was calculated. It was shown that increasing the concentration of inhibitors reduces the enzymatic reaction rate linearly. The kinetics of inhibition by kojic acid was studied and the Michaelis constants calculated. It was found that kojic acid could non-competitively inhibit the tyrosinase action on its substrate, dopamine hydrochlodride under specified conditions.